Karakteristik Komite Audit Pada Audit Report Lag - Pradnyadari Pemayun, Cokorda Istri Mas; Putra Astika, Ida Bagus (E-Jurnal Akuntansi; Vol 31 No 1 (2021), 2021)
This study examines the relationship between the characteristics of the Audit Committee and Audit Report Lag. Audit committee characteristics are measured by several variables, namely the size of the audit committee, the independence of the audit committee, and the audit committee meeting. This research was carried out on manufacturing companies listed on the Indonesia Stock Exchange in 2014-2016. The number of samples used in this study were 44 companies obtained by purposive sampling method. Data analysis techniques were carried out using multiple linear regression analysis techniques. Based on the results of the analysis, it shows that the audit committee characteristics as measured by the size of the audit committee have a significant negative effect on audit report lag. This study also found that the independence of the audit committee had a positive influence and the audit committee meeting had no effect on audit report lag. Keywords: Audit Committee Size; Audit Committee Independence; Audit Committee Meeting; Audit Report Lag.